On the Reflection of Urban Identification in the System of Urbonyms - Suynova Г.С. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2018)
As the process of urbanization gathers pace in the modern Kazakhstan, the city linguisticand-communicative life becomes an inexhaustible source of research for domestic linguists. The urbonyms study is considered a part of onomastics, which focuses on issues of creation and functioning of urbonyms, i.e. names of intracity objects. In Pavlodar there are over 40 groups of such nominations, which are studied by the author of this article, primarily from the linguistic point of view. However, the author proposes to expand the research field of linguistic urban studies attempting to identify interrelation between the city’s urban system and its identity. Such approach to linguistic subject-matter is new to domestic linguistics and is therefore of interest to researchers.